A Moderate Daily Dose of Resveratrol Mitigates Muscle Deconditioning in a Martian Gravity Analog - Mortreux, Marie; Riveros, Daniela; Bouxsein, Mary L.; Rutkove, Seward B. (Frontiers in Physiology, 2019)
While there is a relatively good understanding of the effects of microgravity on human physiology based on five decades of experience, the physiological consequences of partial gravity remain far less well understood. Until recently, no model had been able to replicate partial gravity such as that experienced on Mars (0.38 g), which would be critical to help sustain long-term missions and ensure a safe return to Earth. Recent development of two partial weight bearing (PWB) models, one in mice and one in rats, now allows for quadrupedal partial unloading that mimics Martian gravity. Resveratrol (RSV), a polyphenol most commonly found in grapes and blueberries, has been extensively investigated for its health benefits, including its anti-inflammatory, anti-oxidative, and anti-diabetic effects. In the context of mechanical unloading, RSV has also been shown to preserve bone and muscle mass. However, there is a lack of research regarding its effect on the musculoskeletal system in partial gravity. We hypothesized that a moderate daily dose of RSV (150 mg/kg/day) would help mitigate muscle deconditioning in a Mars gravity analog. Indeed, our results demonstrate that RSV treatment during partial unloading significantly preserves muscle function (e.g., the average change in grip force after 14 days of PWB40 was of −6.18, and +10.92% when RSV was administered) and mitigates muscle atrophy (e.g., RSV supplementation led to an increase of 21.6% in soleus weight for the unloaded animals). This work suggests the potential of a nutraceutical approach to reduce musculoskeletal deconditioning on a long-term mission to Mars.